DETERMINATION OF TRUST AND PURCHASE DECISIONS: ANALYSIS OF BRAND IMAGE AND PRICE (MARKETING MANAGEMENT LITERATURE REVIEW) - Wydyanto, Wydyanto; Rafqi Ilhamalimy, Ridho (Dinasti International Journal of Management Science, 2021)
The purpose of writing a Literature Review Papers is to determine the effect of brand image and price variables on trust and purchase decisions. With qualitative methods and Library Research. The results show that brand image affects on trust, brand image affects on purchasing decision, price affects on trust, price affects on purchasing decision and trust affects on purchasing decisions.